“Much more than second best”: Therapists’ experiences of videoconferencing psychotherapy - Mitchell, Emily (European Journal for Qualitative Research in Psychotherapy, 2020)
This study employs phenomenologically-orientated Thematic Analysis to explore the lived experience of integrative psychotherapists using videoconferencing for psychotherapy. Semi-structured interviews were used to explore the subjective experience of six experienced integrative psychotherapists who use videoconferencing psychotherapy as part of their practice. Thematic analysis identified four themes: ‘Seen and Hidden’, ‘Intimacy and Distance’, ‘Open to Connect’ and ‘Similar but Different Worlds’. This study extends current knowledge in this area and addresses a specific gap in the literature. Its findings suggest that integrative psychotherapists are able to engage online at relational depth: Multi-level contact with their clients via videoconferencing psychotherapy and a working alliance and reparative, transferential processes can be experienced via this medium. The limitations of the medium include the challenges involved in the absence of physical contact, although integrative psychotherapists are still able to work with the body via this medium. Further research is required to understand the strengths and limitations of online work and to gain a deeper, more embodied account of the phenomenon.